(untitled) (Research, Society and Development, 2020)
The benefits bring benefits to the body due to its antioxidant, anti-inflammatory and antimutagenic properties. The antioxidant activity of teas marketed in open markets and industrialized teas in São Luís - MA was evaluated. After the use of Lemon Balm (Melissa officinalis), Bilberry (Peumus boldus), Chamomile (Matricaria chamomilla) and Mint (Mentha) teas by decoction process after liquid-liquid extraction with ethyl chemical reagent (FAE). An antioxidant activity was performed by the DPPH method, which is an organic compound 2,2-diphenyl-1-picrylhydrazyl, where it was used in the analysis of 31.25 to 500 μg/mL of each tea extract. The extracts with the best antioxidant activity were inoculated in tenebrous molybdenum larvae (100 and 200 µg/mL) to test toxicity and protection against oxidative stress induction.The FAE of chamomile and industrial boldo tea has antioxidant activity of 60 and 50% (p <0.05), respectively, and is not yet any of the extracts tested in toxic action larvae. After an induction of oxidative stress, the 100 µg/mL industrial boldo extracts and the 100 µg/mL fairground chamber were able to protect as larvae, maintaining 40% and 50% until the day after inoculation, respectively. As the boldo and chamomile samples show the best results related to antioxidant activities in their industrial products and extracts of these products are not toxic effects on T. molitor larvae, besides promoting the protective effect after induction of oxidative stress.